Три новых вида рода Paraseiulus (Parasitiformes, Phytoseiidae) фауны СССР и переописание P. incognitus Wainstein et Arutunjan, 1967 - Колодочка, Л.А. (Вестник зоологии, 1983)
Three species of the genus Paraseiulus Mum a, 1961 are described as
new, P. (s. str) incognitus Wainstein et Arutunjan, 1967 is redescribed with
lectotype designation.

P. intermixtus sp. n.— closely allied to P. incognitus, distinct in remarkably shorter
dorsal setae, position of second sternal pores on sternal shield posterior margin. dorsal
shield sculpture, ventrianal shield shape and proportions.

P inobservatus sp. closely related lo P. incognitus, differs hy short incrassate
dorsal sctac, dorsal shield sculpture, ventrianal shield shape and proportions. position
of second sernal pores on sternal shield postero-lateral appendages.

P. insignis sp. n.— similar io mentioned species, distinct in the presence of preanal
pores on ventrianal shield, strongly swollen and fainfly sclerotized spermatheca cervix

All the species, that have some common characters — infundibulum coniformly dilated toward spermatheca succulus, dorsal shield net-tuberculate sculpture, form, together
with P. porosus Kolodochka, 1980 and P. erevanicus Wainstein et Arttunjan, 1967, the "incognitus" group. A key to species is given.